1984
DOI: 10.2307/3899631
|View full text |Cite
|
Sign up to set email alerts
|

Livestock Impacts on Riparian Ecosystems and Streamside Management Implications... A Review

Abstract: Historically, riparian vegetation has been defined as vegetation rooted at the water's edge (Campbell and Franklin 1979). Quite often, however, the stream influences vegetation in many ways and well beyond the water line. In lotic systems, the stream is not only responsible for increased water availability, but also for the soil deposition, unique microclimate, increased productivity, and the many consequential, self-perpetuating biotic factors associated with riparian zones. These factors all contribute in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
338
1
7

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 487 publications
(358 citation statements)
references
References 23 publications
12
338
1
7
Order By: Relevance
“…Greater absolute biomass removal from riparian meadows corroborates results from other studies (e.g., Kauffman and Krueger 1984;Gillen et al 1985;Willms 1988) on the importance of riparian meadows as foraging sites for livestock. Given that cattle tend to be more selective at the beginning of a rotational grazing period (Walker et al 1989), the visitation frequency data documented here tend to support the notion that livestock occupy riparian meadows immediately upon initiation of the grazing period.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Greater absolute biomass removal from riparian meadows corroborates results from other studies (e.g., Kauffman and Krueger 1984;Gillen et al 1985;Willms 1988) on the importance of riparian meadows as foraging sites for livestock. Given that cattle tend to be more selective at the beginning of a rotational grazing period (Walker et al 1989), the visitation frequency data documented here tend to support the notion that livestock occupy riparian meadows immediately upon initiation of the grazing period.…”
Section: Discussionsupporting
confidence: 89%
“…Localized overuse can significantly affect plant community composition (Kauffman and Krueger 1984), in turn affecting other rangeland values including wildlife habitat (Schulz and Leininger 1990). Despite their importance, riparian zones have often been overlooked because of their small size relative to the entire landscape (Gillen et al 1985), and accordingly, are more likely to be overgrazed, particularly under season-long grazing systems (Platts 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Photographic records could be used to assess ground cover, representing the amount of plant material (dead or alive) that covers the soil surface, expressed as a percentage. Ground cover, although not representing biomass availability, could be used as an alternative alarm indicator for overgrazing (Kauffman and Krueger 1984). To our knowledge, ground image information has not been used for monitoring montados, though, a preliminary study (Rato et al 2013) where an image processing technique was tested has shown a 95 % correlation between manual and image processing evaluation of vegetation ground cover.…”
Section: Monitoring Grazing Pressure Using Wireless Sensor Networkmentioning
confidence: 98%
“…Because legumes tend to be more sensitive to treading damage than grasses, a shift on pasture composition toward grasses may occur under heavy hoof action with consequent reduction on plant diversity. Damage from treading is typically higher on heavy clay soils and is greatly increased under high soil moisture conditions (Kauffman and Krueger 1984). Treading can also create gaps in the sward, which may be suitable for plant regeneration thus having a positive effect on the establishment of annual and bi-annual species (Metera et al 2010).…”
Section: Variable Interactions-animal Impactsmentioning
confidence: 99%